Role of Intercultural Communicative Competence (ICC) to Improve the Quality of English Language Lecturers in the Digital Era - Jana Sandra; Mira Permata Sari; Baby Poernomo; Nataya Premchaiporn; Mara Elaiza Augustine Flores (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
In this modern era, challenges and competition on a global scale are getting tougher. For this reason, language skills, especially English, are very important as a provision to participate in global competition. English itself has become a unifying language of various nations because it has been used in various countries. Up to the present time, English is actively used by more than 1.75 billion people in the world, both for everyday language and for business and academic needs. The main problem identified in this study was the low ability of Intercultural Communicative Competence (ICC) among the English lecturers in private universities in Jakarta. This study was carried out in the form of a phenomenological approach. The research is defined into two major aspects namely to know how the perspective of Indonesian lecturers on Intercultural Communicative Competence (ICC) and how to improve the lecturers’ abilities on English Language Learning. In-depth interviews were conducted to understand how participants experienced the phenomenon. The research proved that intercultural communicative competence (ICC) plays a significant role in enhancing the quality of the English language lecturers in the digital era.